2011
DOI: 10.1377/hlthaff.2011.0641
|View full text |Cite
|
Sign up to set email alerts
|

Ohio Study Shows That Insurance Coverage Is Critical For Children With Special Health Care Needs As They Transition To Adulthood

Abstract: Nearly 30 percent of young adults with special health care needs in Ohio lack health insurance, compared to 5 percent of the state's children with special health care needs. As children with such needs become too old for Medicaid or insurance through their parents' employer, they face great challenges in obtaining insurance. Lack of insurance is highly predictive of unmet needs, which in turn are predictive of costly hospital-based encounters. Young adults with special health care needs who are uninsured are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
(17 reference statements)
1
13
0
Order By: Relevance
“…YSHCN with private medical insurance or private insurance and Medicaid were more likely to use dental care than uninsured youth (RR=1.15 and RR=1.21, respectively). Adequate medical insurance was the strongest predictor of dental utilization for YSHCN (RR=1.51), which is consistent with other studies on health transitions [10,37]. Although health insurance is not a sufficient condition for dental care use, our findings support policies that enable youth to maintain comprehensive coverage under a parent’s health plan until age 26 – a key feature of the U.S.…”
Section: Discussionsupporting
confidence: 90%
“…YSHCN with private medical insurance or private insurance and Medicaid were more likely to use dental care than uninsured youth (RR=1.15 and RR=1.21, respectively). Adequate medical insurance was the strongest predictor of dental utilization for YSHCN (RR=1.51), which is consistent with other studies on health transitions [10,37]. Although health insurance is not a sufficient condition for dental care use, our findings support policies that enable youth to maintain comprehensive coverage under a parent’s health plan until age 26 – a key feature of the U.S.…”
Section: Discussionsupporting
confidence: 90%
“… 39 Young adults with special health care needs who are uninsured have been shown to delay or forgo care and to have problems getting care. 40 In our study, 4 in 10 non-ambulatory males aged 24-30 reported changing health insurance coverage in the past 12 months as compared to none of the non-ambulatory males aged 16-18 years. The reasons for the high proportion of non-ambulatory males aged 24–30 years who changed their health insurance coverage are unknown; possible explanations include men changing from their parents’ insurance to their own insurance, or qualifying for Medicare or Medicaid.…”
Section: Discussionmentioning
confidence: 49%
“…These outcomes are often the result of preventable lapses in adherence, 4 follow-up, 5 and insurance coverage. 6 Preventing adverse outcomes during transition requires support, especially for youth with special health care needs. In 2011, the American Academy of Pediatrics, the American Academy of Family Physicians, and the American College of Physicians jointly developed a report on transition that includes a set of specific clinical activities recommended for all youth beginning at age 12 7 ; yet, national data reveal that most youth do not receive needed transition services.…”
mentioning
confidence: 99%